COMPARATIVE ANALYSIS OF THE USE OF INTERNAL MEASURES FOR QUALITY ASSURANCE IN PUBLIC AND PRIVATE UNIVERSITIES IN SOUTH EAST NIGERIA - W. N., Rev. Fr. Ofojebe,; V. N., Nwogbo,; Nonso, Anachuna, Obinna, (European Scientific Journal, ESJ, 2015)
The seeming decline in the quality of university education in Nigeria necessitated this study on the comparative analysis of the internal measures that are used in public and private universities in south east geo-political zone of Nigeria for quality assurance. The study adopted the descriptive survey research design. Three research questions and three hypotheses guided the study. The population of the study comprised 29,083 made up of 7,444 lecturers and 21,639 students admitted in the 2011/2012 academic session in the 74 faculties and 413 departments of the 13 universities (five public and eight private) in the south-east geo political zone, Nigeria. The sample of the study comprised 2,106 respondents which were made up of 936 lecturers and 1, 170 students from four universities sampled. The sample was composed through multi-stage sampling technique. Questionnaire developed by the researchers titled â€œStudentsâ€™ Questionnaire on Internal Measures for Quality Assuranceâ€ (SQIMFQA) and â€œLecturersâ€™ Questionnaire on Internal Measures for Quality Assuranceâ€ (LQIMFQA).was the instrument used for data collection. The instrument was validated by three experts, one in Educational measurement and evaluation and the others in Educational planning from the departments of Educational foundations and Educational Management and Policy all in the faculty of Education Nnamdi Azikiwe University, Awka. The Cronbachâ€™s alpha method was used to determine the internal consistency of the items and this yielded a result of 0.74. The researcher with the help of eight research assistants distributed and successfully collected all the 2,106 copies of the questionnaire administered. The research questions were analyzed using the mean, while the hypotheses were tested using z-test at 0.05 level of significance. It was found among others that internal measures for quality assurance of student intake measures, evaluation of studentsâ€™ learning experience and teacher quality measures were not adequately used in both public and private universities in the south-east geo-political zone of Nigeria for quality assurance. Based on the findings, recommendations were made.